A comparison of port-site infiltration with bupivacaine alone vs. bupivacaine plus dexemedetomidine after diagnostic staging laparoscopy - Qureshi, Rabeea Sajid; Alam, Tanveer; Saleem, Huma (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the effects of bupivacaine alone and in combination with dexmedetomidine following staging laparoscopies. Method: The triple-blinded, prospective study was conducted from June to September 2021 at a tertiary care cancer hospital in Lahore, Pakistan, and comprised adult patients having American Society of Anaesthesiologists (grade I-III, weighing >30kg and undergoing diagnostic staging laparoscopy. The subjects were randomised into two equal groups. Group A received 6ml of 2mg/kg bupivacaine at each of the four laparoscopic port sites before skin closure, while group B additionally received 2µg/kg dexmedetomidine. The presence and severity of pain were recorded and assessed at 15 min, 1, 2 and 4 hours as well as at the time of discharge from the post-anaesthesia care unit. The time to first request for rescue analgesia, total morphine consumption, and the occurrence of any side effects during their stay were also recorded. Data was analysed using SPSS 23. Results: Of the 30 patients, 15(50%) were in group A; 10(66.6%) males and 5(33.3%) females with mean age 43.27±7.59 years. There were 15(50%) patients in group B; 12(80%) males and 3(20%) females with mean age 41.36±12.42 years (p>0.05). Of the total, 29(96.66%) patients were classified as American Society of Anaesthesiologists grade II, and 1(3.33%) patient in group A was grade III. There was no significant difference between the groups in any of the outcome measures assessed (p>0.05), and none of the patients experienced any side effect throughout the post-operative stay. Conclusion: The combination of dexmedetomidine and bupivacaine had no significant improvement in pain relief compared to bupivacaine alone. Key Words: Diagnostic laparoscopy, Staging laparoscopy, laparoscopy, Dexmedetomidine, Bupivacaine, Local infiltration, Regional anaesthesia.